MANAGEMENT OF PINK MEALYBUG, MACONELLICOCCUS HIRSUTUS (GREEN) (HEMIPTERA : PSEUDOCOCCIDAE), A MAJOR PEST OF MULBERRY (MORUS ALBA L.) WITH BOTANICALS - MUKHOPADHYAY, S.K.; KUMAR, M.V. SANTHA; SAHA, A.K.; BAJPAI, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Three botanicals were tested individually and in combination to find their effectiveness for management of pink mealy bug, Maconellicoccus hirsutus. Among the treatments consistent reduction of meally bug population was observed with 1.5% Pongamia oil, 2.0% Neem oil and 1.0% Neem oil + Pongamia oil (1 : 1), up to 14 days of spray. Tukra incidence also reduced to a considerable level with the above treatments up to 21 day of spray. Benefit cost ratio of 1.5% Pongamia oil and 1.0% Neem oil + Pongamia oil (1 : 1) treatments are higher, in comparison to chemical control.